Step
*
1
of Lemma
near-inverse-of-increasing-function
.....assertion..... 
1. f : ℝ ⟶ ℝ
2. n : ℕ+
3. M : ℕ+
4. z : ℝ
⊢ ∀[d:ℕ]
    ∀a,b:ℤ.
      ∀k:ℕ+
        (∃c:ℤ. (∃j:ℕ+ [((|f[(r(c))/j] - z| ≤ (r1/r(n))) ∧ ((r(a))/k ≤ (r(c))/j) ∧ ((r(c))/j ≤ (r(b))/k))])) supposing 
           ((z ≤ f[(r(b))/k]) and 
           (f[(r(a))/k] ≤ z) and 
           (∀x,y:ℝ.
              (((r(a))/k ≤ x)
              
⇒ (x < y)
              
⇒ (y ≤ (r(b))/k)
              
⇒ ((f[x] ≤ f[y]) ∧ (((y - x) ≤ (r1/r(M))) 
⇒ ((f[y] - f[x]) ≤ (r1/r(n))))))) and 
           (((M * (b - a)) - k) ≤ d)) 
      supposing a < b
BY
{ ((UniformCompNatInd THEN Auto) THEN (Decide ⌜(M * (b - a)) ≤ k⌝⋅ THENA Auto)) }
1
1. f : ℝ ⟶ ℝ
2. n : ℕ+
3. M : ℕ+
4. z : ℝ
5. [n@0] : ℕ
6. ∀[m:ℕn@0]
     ∀a,b:ℤ.
       ∀k:ℕ+
         (∃c:ℤ. (∃j:ℕ+ [((|f[(r(c))/j] - z| ≤ (r1/r(n))) ∧ ((r(a))/k ≤ (r(c))/j) ∧ ((r(c))/j ≤ (r(b))/k))])) supposing 
            ((z ≤ f[(r(b))/k]) and 
            (f[(r(a))/k] ≤ z) and 
            (∀x,y:ℝ.
               (((r(a))/k ≤ x)
               
⇒ (x < y)
               
⇒ (y ≤ (r(b))/k)
               
⇒ ((f[x] ≤ f[y]) ∧ (((y - x) ≤ (r1/r(M))) 
⇒ ((f[y] - f[x]) ≤ (r1/r(n))))))) and 
            (((M * (b - a)) - k) ≤ m)) 
       supposing a < b
7. a : ℤ
8. b : ℤ
9. a < b
10. k : ℕ+
11. ((M * (b - a)) - k) ≤ n@0
12. ∀x,y:ℝ.
      (((r(a))/k ≤ x)
      
⇒ (x < y)
      
⇒ (y ≤ (r(b))/k)
      
⇒ ((f[x] ≤ f[y]) ∧ (((y - x) ≤ (r1/r(M))) 
⇒ ((f[y] - f[x]) ≤ (r1/r(n))))))
13. f[(r(a))/k] ≤ z
14. z ≤ f[(r(b))/k]
15. (M * (b - a)) ≤ k
⊢ ∃c:ℤ. (∃j:ℕ+ [((|f[(r(c))/j] - z| ≤ (r1/r(n))) ∧ ((r(a))/k ≤ (r(c))/j) ∧ ((r(c))/j ≤ (r(b))/k))])
2
1. f : ℝ ⟶ ℝ
2. n : ℕ+
3. M : ℕ+
4. z : ℝ
5. [n@0] : ℕ
6. ∀[m:ℕn@0]
     ∀a,b:ℤ.
       ∀k:ℕ+
         (∃c:ℤ. (∃j:ℕ+ [((|f[(r(c))/j] - z| ≤ (r1/r(n))) ∧ ((r(a))/k ≤ (r(c))/j) ∧ ((r(c))/j ≤ (r(b))/k))])) supposing 
            ((z ≤ f[(r(b))/k]) and 
            (f[(r(a))/k] ≤ z) and 
            (∀x,y:ℝ.
               (((r(a))/k ≤ x)
               
⇒ (x < y)
               
⇒ (y ≤ (r(b))/k)
               
⇒ ((f[x] ≤ f[y]) ∧ (((y - x) ≤ (r1/r(M))) 
⇒ ((f[y] - f[x]) ≤ (r1/r(n))))))) and 
            (((M * (b - a)) - k) ≤ m)) 
       supposing a < b
7. a : ℤ
8. b : ℤ
9. a < b
10. k : ℕ+
11. ((M * (b - a)) - k) ≤ n@0
12. ∀x,y:ℝ.
      (((r(a))/k ≤ x)
      
⇒ (x < y)
      
⇒ (y ≤ (r(b))/k)
      
⇒ ((f[x] ≤ f[y]) ∧ (((y - x) ≤ (r1/r(M))) 
⇒ ((f[y] - f[x]) ≤ (r1/r(n))))))
13. f[(r(a))/k] ≤ z
14. z ≤ f[(r(b))/k]
15. ¬((M * (b - a)) ≤ k)
⊢ ∃c:ℤ. (∃j:ℕ+ [((|f[(r(c))/j] - z| ≤ (r1/r(n))) ∧ ((r(a))/k ≤ (r(c))/j) ∧ ((r(c))/j ≤ (r(b))/k))])
Latex:
Latex:
.....assertion..... 
1.  f  :  \mBbbR{}  {}\mrightarrow{}  \mBbbR{}
2.  n  :  \mBbbN{}\msupplus{}
3.  M  :  \mBbbN{}\msupplus{}
4.  z  :  \mBbbR{}
\mvdash{}  \mforall{}[d:\mBbbN{}]
        \mforall{}a,b:\mBbbZ{}.
            \mforall{}k:\mBbbN{}\msupplus{}
                (\mexists{}c:\mBbbZ{}
                    (\mexists{}j:\mBbbN{}\msupplus{}  [((|f[(r(c))/j]  -  z|  \mleq{}  (r1/r(n)))
                                  \mwedge{}  ((r(a))/k  \mleq{}  (r(c))/j)
                                  \mwedge{}  ((r(c))/j  \mleq{}  (r(b))/k))]))  supposing 
                      ((z  \mleq{}  f[(r(b))/k])  and 
                      (f[(r(a))/k]  \mleq{}  z)  and 
                      (\mforall{}x,y:\mBbbR{}.
                            (((r(a))/k  \mleq{}  x)
                            {}\mRightarrow{}  (x  <  y)
                            {}\mRightarrow{}  (y  \mleq{}  (r(b))/k)
                            {}\mRightarrow{}  ((f[x]  \mleq{}  f[y])  \mwedge{}  (((y  -  x)  \mleq{}  (r1/r(M)))  {}\mRightarrow{}  ((f[y]  -  f[x])  \mleq{}  (r1/r(n)))))))  and 
                      (((M  *  (b  -  a))  -  k)  \mleq{}  d)) 
            supposing  a  <  b
By
Latex:
((UniformCompNatInd  THEN  Auto)  THEN  (Decide  \mkleeneopen{}(M  *  (b  -  a))  \mleq{}  k\mkleeneclose{}\mcdot{}  THENA  Auto))
Home
Index